Integration of Foreign Languages in Study Process - Liepa, Diāna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the article is to describe language learning conditions for improvement of students learning experience. The practical task is to promote students' knowledge about language learning, foreign language learning pedagogical conditions and its transformation in the study process. The study is carried out in previous research analysis to gain insight into the overall situation of the foreign language studies in Latvia. The research provides an explanation of students’ learning and teaching conditions, the results show that a unified foreign language study conception should be developed and implemented in practice. Research Methods Theoretical methods: analysis of scientific and methodological literature, modelling. Empirical research methods: methods of data acquisition – observation, experimenting, data analysis by using the data processing software SPSS 17.0.The research is based at the Riga Teacher Training and Educational Management Academy RTTEMA Pre-School and Primary School Teacher programmes.